The Efforts of Islamic Religious Education Teachers in Fostering Student Morals - Muhammad Muslih (Institut Agama Islam Negeri (IAIN) Curup, 2021)
This research is based on the number of students whose morals are not good because of the free association from the family environment as well as the lack of support in guiding; therefore the role of Islamic religious teachers is needed in these conditions. In several places or the media, we often see how the morals of children are not polite in their interactions, both in terms of actions and words. Islamic religious teachers should play an active role in building student morals, especially in schools. This phenomenon needs handling, especially for Islamic religious education teachers, even though it is only a few hours at school to guide at least there are efforts to improve student morality. This study aims to determine the role of teachers in mentally coaching students, and to know closely how Islamic religious teachers are trying to build the morals of junior high school students. The method used in this study uses field research methods (Field Research) to collect research data using, observation techniques, interviews, document study. After the data is collected, the researcher processes it with qualitative descriptive analysis. This research effort shows that Islamic religious teachers have done their best in guiding students' morality, the efforts made by Islamic religious teachers are to collaborate with related parties, the results of efforts to build morals at SMP Nuha are good seen from the way they act, dress, and speak. the Islamic one.